Enhancing Students Psychological Well-being in Islamic Boarding Schools: The Impact of Prophetic Values-Based Group Counseling - Khusumadewi, Ari; Hannurawan, Fattah; Hambali, IM; Atmoko, Adi (KONSELOR, 2023)
This study analze the impact of group counseling sessions based on prophetic values on the psychological well-being of students in Islamic boarding schools in East Java, Indonesia. Sixty students from five schools participated in an experimental design involving pre-tests and post-tests. The intervention included seven group guidance sessions led by non-professional counselors, emphasizing prophetic values. A 22-item scale assessing various aspects of psychological well-being was used, and the effectiveness of the intervention was analyzed using a one-way ANOVA test. The results showed significant improvements in the psychological well-being of the experimental group, with higher mean scores post-intervention compared to the control group. The study highlights the critical role of peer relationships in the psychological health of students in these schools. The successful incorporation of prophetic values in the intervention aligns with the students' cultural and religious background, enhancing its effectiveness. The findings suggest the importance of including such value-based guidance programs in the curriculum of Islamic boarding schools, tailored to their unique educational environment. The study also recommends training for mentors in guidance skills to better support student well-being in these settings.